Manufacture of Glass Foam by Predominantly Direct Microwave Heating of Recycled Glass Waste - AXINTE, Sorin Mircea; Paunescu, Lucian; Dragoescu, Marius Florin; Sebe, Ana Casandra (Discoveries in Agriculture and Food Sciences, 2019)
The paper presents authors’ contribution to the improvement of the manufacturing technique of foam glass using the microwave energy. Due to the physical and mechanical characteristics, this material, obtained by the sintering process of waste glass at high temperature, constitutes a viable replacer of existing similar materials, used especially in construction. Unlike the conventional heating methods used worldwide, the company Daily Sourcing & Research SRL Bucharest tested lately microwave heating techniques in the manufacturing process of foam glass. In the paper it is presented an original method based on the feature of the powder mixture composed by waste glass (over 97 wt.%) and the foaming agent (calcium carbonate) to absorb the microwave energy and convert it to heat since the ambient temperature, using a silicon carbide and silicon nitride (80/ 20 weight ratio) crucible with thin wall (2.5 mm), which allows both a preponderantly direct heating and partially an indirect heating of the material. The main parameters of the process (specific consumption of energy, heating speed, process temperature and duration) were significant improved compared to the previous experiments.